2016
DOI: 10.1021/acs.chemmater.6b01676
|View full text |Cite
|
Sign up to set email alerts
|

Retrosynthetic Co-Templating Method for the Preparation of Silicoaluminophosphate Molecular Sieves

Abstract: 1,5-(1,4-diazabicyclo[2.2.2]octane)pentyl dibromide (diDABCO-C5)13.0 g (0.06 mol) of 1,5-dibromopentane was dissolved in 50 mL ethanol and added droop-wise to a solution under stirring at 50 °C of 33.6 g (0.30 mol) of 1,4-diazabicyclo[2.2.2]octane (DABCO) dissolved in 100 mL ethanol. The mixture was refluxed for 24 hours. Once cold, the excess of ethanol was removed on a rotary evaporator leaving yellow oil. Subsequently cold

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 64 publications
2
33
0
Order By: Relevance
“…prepared with the same co-templates. 30 Most signals observed in STA-20 are closely similar to those non-equivalent C atoms assigned to diDABCO-C6 in STA-20. However, for each expected non-equivalent C in diDABCO-C6 in STA-20, two peaks can be resolved in the spectrum.…”
Section: Structure Solution and Refinement For As-prepared Sta-20mentioning
confidence: 61%
See 2 more Smart Citations
“…prepared with the same co-templates. 30 Most signals observed in STA-20 are closely similar to those non-equivalent C atoms assigned to diDABCO-C6 in STA-20. However, for each expected non-equivalent C in diDABCO-C6 in STA-20, two peaks can be resolved in the spectrum.…”
Section: Structure Solution and Refinement For As-prepared Sta-20mentioning
confidence: 61%
“…Similar effects were previously observed for co-templated syntheses of SAPOs STA-18 (SFW) and STA-19 (GME). 30 Other materials with frameworks belonging to the ABC-6 family, such as SAPO STA-18 and STA-20, can also be successfully used as seeds for STA-20. We speculate that the similar structural layers present in these materials play a role in the nucleation of STA-20 crystals.…”
Section: Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…The two additional frameworks are the SFW and the SWY frameworks, which correspond to two silicoaluminophosphates that were recently synthesised by Wright and co-workers (STA-18 -SFW and STA-20 -SWY). 61,62 Like all other structures, these two frameworks were optimised in pure-AlPO 4 composition. The setup of the structure optimisations was chosen on the basis of previous benchmarking work, 63,64 using the CASTEP code with on-the-fly-generated ultrasoft pseudopotentials, 65 the PBE functional 66 in conjunction with the dispersion correction devised by Tkatchenko and Scheffler, 67 and an energy cutoff of 700 eV.…”
Section: Computational Detailsmentioning
confidence: 99%
“…Based on this premise, we may expect a cooperative structure-directing effect of OSDAs and crystal seeds under certain conditions. Inspired by the cooperative structure-directing effect of two different OSDAs [24][25][26][27][28][29], various syntheses employing a combination of organic molecules and solid seeds have been reported. For example, Valtchev et al [30] reported the "inductive effect" of as-synthesized UTD-1 seeds on the crystallization of SSZ-24 zeolites, where the addition of UTD-1 seeds accelerated the zeolite nucleation and led to the formation of pure and well-crystallized SSZ-24.…”
Section: Introductionmentioning
confidence: 99%